Learning AIDS in Singapore: Examining the Effectiveness of HIV/AIDS Efficacy Messages for Adolescents Using ICTs - Chib, Arul (2015)
The objective of this study was to assess adolescents‘ receptivity to the use of new interactive media for dissemination of sensitive health messages. We propose a conceptual framework based on the Extended Parallel Process Model (EPPM) to design a gamebased HIV/AIDS intervention for adolescents. Amongst key findings, we found that Game Play led to changes in attitudes and intentions